Correlation of serum calcium with blood pressure and Body Mass Index (BMI) among ischemic stroke patients in Bangladesh - Sharmin, Nazia; Al-Mahmood, Abu Kholdun; Sultana, Nasima (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Background: Ischemic stroke more commonly occurs in hypocalcemic patients and presented with more severe clinical symptoms. Objective: We sought to observe the correlation of serum calcium with blood pressure and BMI among stroke patients in Bangladesh. Methods: We performed a case-control study using the Department of Biochemistry at Dhaka Medical College, Dhaka, Bangladesh from January 2014 to December 2014. The case were defined as patients diagnose with an acute ischemic stroke, and controls were defined as healthy subjects. In this identified population, 15 cases were matched on age and sex to 50 control subjects. The information regarding age, serum calcium level, height and weight of both cases and controls were taken to calculate BMI. Systolic and diastolic blood pressure (SBP and DBP) from the subject are taken to investigate the history of hypertension. Result: Serum calcium has statistically significant with a negative correlation with DBP (r =-0.335, p=0.017) and BMI (r =-0.426, p=0.002). A negative correlation between serum calcium and SBP also can be observed (r= - 0.194, p= 0.176). Conclusion: Findings of this study concludes that hypocalcemia is found to be negatively correlated with blood pressure and BMI among ischemic stroke patients in Dhaka, Bangladesh.